Atrial transseptal left ventricular lead implantation for cardiac resynchronization therapy using arteriovenous loop technique. Issue 7 (30th April 2018) - Liang, Yixiu; Zhou, Daxin; Wang, Jingfeng; Qin, Shengmei; Chen, Xueying; Su, Yangang; Ge, Junbo
Abstract: To date, several techniques for transseptal left ventricular (LV) endocardial pacing for cardiac resynchronization therapy (CRT) have been proposed in patients for whom routine transvenous LV pacing is infeasible. These techniques are of varying difficulty and complexity, and some requires devices not easily accessible. We herein report a simple, safe and effective approach of atrial transseptal LV lead implantation using arteriovenous loop technique in a patient for whom transvenous LV implantation lead had failed.